Nation State, Marketisation of Social Services and Uncertainty of Livelihood in India. (1st April 2015) - ,; ,
Abstract : An attempt has been made to highlight some important issues in order to examine the inclusiveness of growth during the era of neoliberalism in India. The article is an attempt to examine the changing role of State within the capitalistic economic structure: how Indian State, which as an inseparable part of international capitalism, has shifted its path from welfare or Interventionist State to laissez-faire neoliberal State. The retreat of the State causes the marketisation of health and educational facilities, which has brought these two significant social services to the market as attractive profit earning commodities. The process of commodification of these services does lead to the deterioration and inaccessibility of these facilities to the masses. The article also scrutinises the question of livelihood through the study of changing structure of employment. The distribution of population employed in various activities and change in the status of employment after the introduction of neoliberal policies are also examined. The process of casualisation and informalisation of livelihood opportunities is also studied in order to grasp the extent of relative surplus population in India. The question of absolute reserve army of labour (wholly unemployed population) examined through the study of workers who are eligible for work but unable to get any work due to jobless growth process in India. The development of an imported industrialisation process has resulted in the increase in proportion of constant capital (machines and related equipments) relative to variable (human labour) capital in manufacturing sectors. In the whole discussion on employment and unemployment, an attempt has been made to apply the Marxian conception of reserve army of labour on Indian working population in order to examine the emerging working-class structure.